1984
DOI: 10.1148/radiology.153.1.6473778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gadolinium-DTPA on the magnetic relaxation times of normal and infarcted myocardium.

Abstract: Acute myocardial infarctions were produced in 11 dogs by ligation of the left anterior descending coronary artery. Twenty-four hours after ligation, 0.35 millimoles per kilogram of Gd-DTPA was injected intravenously, followed by cardiectomy either 90 seconds (3 dogs) or 5 minutes (5 dogs) later. The remaining 3 dogs had cardiectomy without injection of Gd-DTPA at 24 hours after coronary occlusion. The 3 dogs that did not receive Gd-DTPA had longer T1 and T2 relaxation times in infarcted myocardium than in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(54 citation statements)
references
References 0 publications
5
45
0
4
Order By: Relevance
“…[14][15][16][17][18] In this study, the inhibitory effect of the β-blocker carvedilol on myocardial fibrosis in a hamster model of progressive dilated cardiomyopathy (TO2: Bio 53.58 hamster) was assessed by comparing the changes in LVDd and EF on echocardiography as well as MRI parameters (left ventricular myocardial volume, the enhanced area, and the relationship between the enhanced area and fibrosis on histopathological examination).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] In this study, the inhibitory effect of the β-blocker carvedilol on myocardial fibrosis in a hamster model of progressive dilated cardiomyopathy (TO2: Bio 53.58 hamster) was assessed by comparing the changes in LVDd and EF on echocardiography as well as MRI parameters (left ventricular myocardial volume, the enhanced area, and the relationship between the enhanced area and fibrosis on histopathological examination).…”
Section: Discussionmentioning
confidence: 99%
“…Wesbey et al 21 showed increased T 1 shortening in transiently ischemic canine myocardium compared with normal tissue. In a canine model, after varying length of coronary occlusion and reperfusion, the size and three-dimensional shape of hyperenhancement correlated closely with irreversible damage defined by triphenyltetrazolium chloride staining.…”
Section: Hyperenhancement and Myocardial Viabilitymentioning
confidence: 94%
“…Recently, the time course and geometry of these alterations have been described (59) by late contrast-enhanced MRI, an imaging technique using injected gadolinium-diethylenetriamine pentaacetic acid (an extracellular contrast agent), which results in late high-resolution images in which myocardial damage appears hyperenhanced (Fig. 1c) (165,167). In this study, consistent ventricular dilation, together with changes in LV shape leading to an increased curvature radius, was shown in dogs subjected to coronary occlusion.…”
Section: Myocardial Wall Stressmentioning
confidence: 99%